Dignity and Health - Jacobson, Nora, 1964- (Book collections on Project MUSE., 2012)
In these hard times of global financial peril and growing social inequality, injuries to dignity are pervasive. "Indignity has many faces," one man told Nora Jacobson as she conducted interviews for this book. Its expressions range from rudeness, indifference, and condescension to objectification, discrimination, and exploitation. Yet dignity can also be promoted. Another man described it as "common respect," suggesting dignity's ordinariness, and the ways we can create and share it through practices like courtesy, leveling, and contribution. Dignity and Health examines the processes and structures of dignity violation and promotion, traces their consequences for individual and collective health, and uses the model developed to imagine how we might reform our systems of health and social care. With its focus on the dignity experiences of those often excluded from the mainstream--people who are poor, or homeless, or dealing with mental health problems--as well as on vulnerabilities like age or sickness or unemployment that threaten to make us all feel "less than," Dignity and Health recognizes dignity as a moral matter embedded in the choices we make every day